DIASPORA FAMILY VIEWS ON LEARNING LATVIAN IN DISTANCE LEARNING CLASSES BY THE LATVIAN LANGUAGE AGENCY - Krastiņa, Linda; Zariņa, Sandra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
8% of the population whose native language is Latvian live outside Latvia in many countries of the world. With the concern for the preservation of Latvian it is disturbing that less than a half of Latvian diaspora families speak Latvian at home, therefore children have a weak proficiency of Latvian or lack it altogether. What is positive about the present situation is that almost all Latvians living in foreign countries wish their children to learn Latvian and choose distance learning classes for language acquisition and improvement, including those provided by the Latvian Language Agency (henceforth – LLA). The aim of the present research is clarifying the motivation of diaspora families to choose for their children distance learning classes of Latvian provided by the LLA and investigating the views of the families on the role of distance classes in the process of learning Latvian. For research data collection, a digital survey questionnaire was compiled and e-mailed to all families participating in distance classes of learning Latvian organized by the LLA in different countries of the world. The research reveals that the majority of the surveyed family children do not attend weekend Latvian schools and prefer regular, systemic language learning classes under the guidance of professional teachers from Latvia. The families admit that distance classes are a convenient mode of language learning, yet the greatest challenges in teaching and sustaining Latvian outside Latvia are the lack of the Latvian linguistic environment and lack of time for engaging with the child, whereas those in distance learning are children’s busyness and lack of motivation for language learning.